Depletable Energy, Intermediate Goods Quality, and Sustainable Growth. Issue 13 (20th October 2020) - Tang, Zhaoxi; Li, Chuanzhong; Xiao, Wen
ABSTRACT: In this article, we attempt to develop a four-sector endogenous growth model with depletable energy resources to study how energy resource depletion and R&D would affect long-run economic growth. We apply the Schumpeterian approach of vertical innovation to characterize technological progress by the efficiency improvement in intermediate goods. We obtain the social optimal equilibrium of this economic system and discuss the conditions for the existence of balanced growth path. We also conduct stability analysis of the optimal long-run balanced growth path and come up with some appropriate policy recommendations.